Acute Anterior Uveitis with HLA-B27 Positivity after Corneal Cross-Linking with Previous Intrastromal Corneal Ring Segment. (21st November 2022) - Khan, Asher; McGuffey, Charles D.; Melson, Andrew T.; Riaz, Kamran M.
Abstract : Purpose . To describe a case of acute anterior uveitis (AAU) with HLA-B27 positivity following epithelium-off corneal cross-linking (CXL) in a patient with a previous intrastromal corneal ring segment. Observations. A 28-year-old male with keratoconus (KCN) developed ophthalmalgia, perilimbal injection, hypopyon, and decline in corrected distance visual acuity (CDVA) 3 days after CXL. A working diagnosis of inflammatory versus infectious AAU was made, and the patient was treated with topical tobramycin, polymyxin B/trimethoprim, prednisolone, and oral valacyclovir. Clinical appearance and CDVA improved, ultimately returning to baseline by two weeks postoperatively. Diagnostic laboratory workup revealed HLA-B27 positivity. Conclusions and Importance. A comprehensive laboratory workup is helpful to identify potential causative and associated systemic conditions when encountering AAU after CXL. Given the overlap in patient demographics for KCN and HLA-B27 positivity, clinicians should consider this entity in the differential diagnosis and treatment of such cases.